PENERAPAN METODE PROFILE MATCHING PADA PEMILIHAN DOSEN PENERIMA BEASISWA STUDI DOKTORAL - Dina Maulina (Jurnal Mantik Penusa, 2018)
Doctoral study programs or S3 courses are demands and requirements for lecturers. Due to the demands of the profession to be more qualified to carry out the tasks of tridharma education, namely teaching, research and community service. In addition, the need for campus accreditation is also to keep it good and getting better. With this motivation, the lecturers try to continue the S3 study program with a scholarship program both government and internal campus. AMIKOM University collaborates with S3 scholarships with UTeM (Universiti Teknikal Malaysia Melaka) and UMP (Universiti Malaysia Pahang). Lecturers who get the scholarship are also selected according to the criteria determined by the YIKYAKARTA AMIKOM University. The party that chooses the lecturer is in the PSDM section. In the election it was still done manually by matching or selecting criteria determined by the campus by fulfilling the criteria possessed by the lecturers who proposed the scholarship program. The method that will be used to select this is the Profile Matching or GAP method, which is one method of solving problems that provide ranking to the alternatives chosen based on predetermined criteria.